Effect of Beauveria bassiana and Metarhizium anisopliae on Hypothenemus hampei (Coleoptera: Scolytidae) populations emerging from fallen coffee fruits on the soil - BERNAL-U., MARTHA GLADYS; BUSTILLO-P., ALEX-E.; CHAVES C., BERNARDO; BENAVIDES-M., PABLO (Revista Colombiana de Entomología, 1999)
The fallen infested coffee herries are the main cause of reinfestation by the coffee berry borer (cbb). Hypothenemu.s. hampei (Ferrari). in coffee plantations at the end of the harvest period. Beauveria bassiana (Balsamo) Vuillemin, is the main natural mortality factor of cbh present in all the Colombian coffee regions infested by this insect, on the other hand, Metarhizium anisopliae (Metschnikoff) Sorokin. is considered an entomopathogen that could have an effect on cbb. This research was aimed to evaluate the effect of soil sprays of the entomopathogens B. bassiana and M. anisopliae, on borers emerging from fallen berries through time. The study was conducted at the Experiment Substation "Maracay" of Cenicafe, near Armenia, Colombia, where two coffee plots of 5000 m= of the Colombian variety in the third harvest were selected; the two species of fungi were evaluated separately in one plot. Nine treatments with ten replications including the control were arranged in each plot under a complete randomized design. The experimental plot consisted of nine trees on which only green uninfested herries were left in an optimal stage for cbh attack: the central tree in this plot was selected as the experimental unit and was completely covered by a fine screen code to avoid the escape or entrance of insects. Conidia used from both fungi were suspended in emulsified oil and water using a dosage of 1 x 10" conidia/tree. On the soi 1 under each tree. used as experimental tuna, 350 coffee infested herries were deposited to serve as the source for aerial infestation of the trees. Treatments consisted of the spray of the fungus to the base of the trees the same day of infestation. and 2, 5, 10, 15. 20. 25 and 30 clays after infestation. The evaluation was made 30 clays after treatments registering the infection hv both fungi no cbb present on infested herries on the branches of the trees.  Results showed that the proposed methodology is adequate to simulate the emergence of borers from infested herries fallen on the soil and to evaluate treatments against the borer on the soil. Infection levels of hoth fungi un cbb were the highest during the first five days. reaching nearly 30% for B. bassiana and 11 % for M. anisopliae; however, the infection decreased and again reached a new peak towards the 25'-day evaluation with 24.3% for B. bassialla and 7.7% for M. onisopliae. These results can he explained bv the phenomenon of microcoidiation or the formation of propagules in microcycles in the soil by these entornopathogens. due probably to the accumulation of infected conidia un insects that infect others to perpetuate the microorganism. In relation to the recovery of these fungi from soil, it was found to be in agreement with the results on the infection of un berries on the trees. The two species were recovered even after two months and fluctuation in numbers of colony-forming units was due probably to the rain precipitate) during the study period and the fungus microconidiation. These fungi can remain infective in the soil for many days and can increase their inoculum Os was shown in this study without the presence of the host insect. B. bassiana \vas shows to he more infective than anisopliae something that was nos expected at the stars of this research. The efficiency of these fungi could be increased it improvements are made to the formulations, using a granulated formolation to avoid drainage of the conidia from the soil during heavy rainy seasons.